Negotiating style: Headscarf and cultural visibility in urban Turkey - Korkmaz, Emine Merve (My University, 2017)
Ever since Muslim women started to be visible with their headscarves in urban life, they became an essential topic for several controversies. The discussions usually centered around various causes and motives on using the headscarf ranging from religion, urbanization, modernization, migration, conservatism etc. Today, the main discussion topic is on visibility and choices of clothing. There are diverse interpretations on headscarved women and as long as differences are present, discussions are not going to end. Yet, headscarved women have different stories and each dispute causes new and transformed voices to emerge. The purpose of this study is to illustrate difference within the narratives of headscarved women in urban Turkey and understand them “from inside” as much as possible. This study is based on a qualitative methodological approach and relies on twelve semi-structured interviews in order to meet this ethnographic agenda. After an examination of the interviews, three separate, but interrelated narratives emerged. I differentiated the three narratives using the following themes: ‘appearance and fashion’, ‘representation and change’, ‘criticism’, and ‘self and other’. The themes analysed in this study highlight the complexity of the discussion of headscarved women. Most of the analyses on headscarved women evaluate the current situation as if it is frozen in time and by focusing on the increasing visibility of the headscarf in public sphere as part of a political agenda in one way or another. Whereas in this study I emphasize the need to engage with individual experiences and stories in order to reflect and analyse the complexity of the issue by highlighting the element of change. My argument is that headscarved women are different individuals changing through urban life. In this context, I aim to demonstrate the diversity within fractions of identities from elapsing experiences.

Müslüman kadınlar başörtüleriyle kent hayatında görünür olmaya başladığından beri çeşitli tartışmaların merkezinde yer almışlardır. Genellikle bu tartışmalarda başörtüsü kullanmanın sebep ve motivasyonları din, kentleşme, modernleşme, göç, muhafazakarlık gibi konular ile birlikte ele alınmıştır. Bugün ise genel tartışma konusu görünürlük ve giyim tercihleri üzerinedir. Başörtülü kadınlar üzerine muhtelif yorumlar vardır ve farklılıklar var olduğu sürece bu tartışmalar sona ermeyecektir. Fakat başörtülü kadınların farklı hikayeleri vardır ve her bir tartışma yeni ve dönüşmüş seslerin ortaya çıkmasına sebep olmaktadır. Bu çalışmanın amacı, kentsel Türkiye’deki başörtülü kadınların anlatıları aracılığıyla farklılıkları göstermek ve onları olabildiğince “içeriden” bir bakışla anlamaya çalışmaktır. Bu çalışma nitel araştırma yöntemine göre hazırlanmış ve etnografik gündemi elde etmek amacıyla on iki yarı yapılandırılmış mülakat yapılmıştır. Mülakatların incelenmesinin ardından ayrı, ama birbirleriyle ilişkili üç anlatı ortaya çıkmıştır. ‘görünüm ve moda’, ‘temsil ve değişim’, ‘eleştiri’ ve ‘ben ve öteki’ temalarıyla üç anlatı birbirinden ayrıştırılmıştır. Bu çalışmada analiz edilen temalar başörtülü kadın tartışmasının karmaşıklığına dikkat çekmektedir. Başörtülü kadınlar hakkındaki analizlerin çoğu o durumu sanki zaman içerisinde sabitmiş gibi ve başörtüsünün kamusal alanda artan görünürlüğünü tek ya da farklı yönde siyasi gündemin bir parçasıymış gibi ele almaktadır. Halbuki ben bu çalışmada değişim etkenine odaklanarak meselenin karmaşıklığını yansıtmak ve analiz etmek için bireysel deneyim ve hikayelerle hareket etmenin gerekliliğine vurgu yapıyorum. Böylelikle, başörtülü kadınların kent hayatında değişmekte olan birbirinden farklı bireyler olduklarını savunuyorum. Bu bağlamda amacım, akışkan deneyimlerdeki çeşitliliği kimlik kesitleri ile göstermektir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2017
Keywords: Headscarf; Headscarved women; Change; Diversity; Appearance; Identity